(untitled) (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study is to evaluate the hypoglycaemic properties and preliminary phytochemical screening of Uveria chamae. The hypoglycaemic properties of Uveria chamae was assessed on normoglycaemic rat that received single dose of the extract at 250 and 500 mg/kg body weight and blood glucose levels estimated at 2, 4, and 6 hours (single dose study). The hypoglycaemic property of the extract was also evaluated in normoglycemic rats by oral glucose tolerance test. Phytochemical screening of the extract for the presence of secondary metabolites was performed with standard methods. The extract showed a significant (p<0.05) reduction in blood glucose levels at 2h and 6h compared to control. The oral glucose tolerance test result also showed a significant decrease (p<0.05) in blood glucose levels . The study showed that the extract, Uveria chamae has hypoglycaemic properties which may be accounted for by the presence of the phytochemicals.